Implementasi Peraturan Kode Etik Notaris dalam Menjalankan Profesi Kepada Masyarakat - Wibowo, Rifdah Oktavia; Aminah, Aminah (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Notaries are public officials and professions who have the authority to make authentic deeds for people who need their services. These services are interpreted in a broad context, which includes not only making authentic deeds, legalizing personal letters, or providing legal advice related to notarial matters, but apart from that, notaries are also obliged to apply professional ethics in providing services to clients. The problem discussed in this journal is the implementation of professional ethics by notaries and legal sanctions given to notaries who do not implement professional ethics in providing services to clients. The research method used for this journal research is normative legal research with research using primary and secondary legal materials. The results of this research indicate that notaries must pay attention to professional ethics in providing services to clients. Notary professional ethics are regulated in the Notary Code of Ethics and UUJN. This aims to ensure that the notary can maintain his honor and dignity in front of clients.